The erector spinae plane block: a narrative review - Pablo Kot; Pablo Rodriguez; Manuel Granell; Beatriz Cano; Lucas Rovira; Javier Morales; Ana Broseta; Jose De Andrés (Korean Journal of Anesthesiology, 2019)
Regional anesthesia and pain management have experienced advances in recent years, especially with the advent of fascial plane blocks. The erector spinae plane block is one of the newest techniques to be described. In the past two years, publications referring to ESP block have increased significantly. The objective of this review is to analyze the articles about ESP block that have been published to date. We performed a search in the main databases and identified 368 articles. After a selection of the relevant articles, 125 studies were found eligible and were included in the review. The ESP block is performed by depositing the local anesthetic in the fascial plane, deeper than the erector spinae muscle at the tip of the transverse process of the vertebra. Many cases of its use have been described with satisfactory results in the treatment of both acute pain and chronic pain. The applicability of the technique covers many clinical scenarios. Of the 98 case reports reviewed, 12 and 87 articles, respectively described the technique as a treatment for chronic pain and acute pain. The single-shot was the most frequently used technique. As described in the articles published to date, the technique is easy to perform and has a low rate of complications. However, despite the effectiveness of the technique, further studies are necessary to obtain more evidence of its actions.